Selamatan Bayi Versi Orang Jawa: Kajian Linguistik Antropologis - Arif Budiman; Ari Wulandari; Noni Sukmawati (Sasdaya: Gadjah Mada Journal of Humanities, 2022)
Selamatan bayi is a form of gratitude and a prayer request for congratulations for the baby. This study aims to describe the local wisdom of selamatan bayi using an anthropological linguistic approach to the contextual design of Javanese tradition. Data collection refers to the technique of recording, participatory observation, and interviews. The results of this study prove that selamatan bayi has a philosophical meaning based on Javanese cultureThere are seven kinds of selamatan bayi among the Javanese, namely (1) brokohan (birthday greetings), (2) sepasaran (5th birthday celebration), (3) selapanan (35-day baby celebration), (4) telonan (3 months birthday greetings), (5) pitonan (7 months of baby's birth), (6) setahunan (1 year of baby's birth), and (7) aqiqah (selamatan bayi for Javanese Muslims). The local wisdom of Javanese in selamatan bayi can be seen from five things, namely (1) the definition, (2) types, (3) ubarampe ‘equipment’, such as sega ingkung, sega gudangan, bubur abang putih, and so on; (4) the method of implementation, and (5) the development of the times. In every selamatan bayi contains the local wisdom of the Javanese to always maintain a balance between human relationships, the natural environment, and God.